La promoción de la salud y los contextos de vulnerabilidad frente al VIH/sida en trabajadoras sexuales. una revisión narrativa (2021)
Women sex workers have different characteristics and attributes, based on the performance of their work and the knowledge they have of preventive and risk practices against HIV; In this sense, each of the social determinants that this population has and its social stigma are taken into account, in such a way the present work establishes the relationship that exists in the approaches of various authors, so that a narrative review of the literature was carried out in order to synthesize findings reported in scientific research on health promotion actions in the context of vulnerability to HIV / AIDS and sexually transmitted diseases in sex workers, therefore it was obtained as a result that the workers sexual do not carry out the best HIV prevention practices, since access presents institutional barriers for the complete counseling of the pathology, which is why it is concluded that a more humanized treatment is lacking in health professionals and greater support in the creation of strategies of national entities.